Antibiotic misuse among university students in western and eastern China: a cross-sectional survey. (December 2017) - Peng, Dandan; Wang, Xiaomin; Wang, Weiyi; Xu, Yannan; Sun, Chenhui; Zhou, Xudong
Abstract: Background: Antimicrobial resistance (AMR) is one of the greatest threats to public health in China. The primary cause of AMR is antibiotic misuse, especially used for self-limiting illnesses. Little is known about regional differences of antibiotic-misuse behaviors in China. We aimed to explore such behaviors among university students in western and eastern China. Methods: The participants were recruited from universities in Guizhou, a less developed province in western China, and from Zhejiang, a more developed province in eastern China, using a cluster random sampling method. A validated, self-administered questionnaire was designed to collect data, and the χ 2 test and logistic regression were adopted to assess the associations between region and antibiotic misuse. Findings: A total of 2073 university students from Guizhou and 1922 from Zhejiang completed questionnaires. Students in Guizhou had lower household income, parents' education, and urban residence proportion than those in Zhejiang. Compared with those in Zhejiang, students in Guizhou had higher antibiotic use prescribed by doctors (79·8% vs 56·2%) and self-medication (33·0% vs 16·1%). The students in Guizhou were more likely to buy over-counter antibiotics (73·9% vs 63·4%), ask for antibiotics from doctors (21·4% vs 15·6%), and use antibiotics prophylactically (29·9% vs 15·7%). Adjusted models also showed that less developed region was associated with higher antibiotic misuse behaviours, including antibiotic use prescribed by doctors (odds ratio 2·95; 95% CI 1·68–5·18; p<0·0001), self-medication (3·00; 1·84–4·90; p<0·0001), buying over-counter antibiotics (1·71; 1·36–2·15; p<0·0001), and taking antibiotics prophylactically (2·28; 1·89–2·76; p<0·0001). Interpretation: Misuse of antibiotics for self-limiting illnesses by well-educated young adults was very high in these two regions but most serious in less-developed western China. A campaign is urgently needed for rational prescribing of antibiotics by doctors, enforcing restrictions on over-the-counter antibiotics, and to educate the general public about the management of self-limiting illness. Funding: Zhejiang University Zijin Talent Programme.